Teaching Participation in Occupations to First Year Occupational Therapy Students: An Action Research Study. (February 2013) - Ghul, Rayya; Marsh, Ian
Introduction: This article describes the development of a first year occupational therapy module, 'Participation in Occupations', and the design and development of a mediating tool, Contexts of Participation: the Critical Thinking Tool, in a British university. Method: Using an action research process, the module content, learning and teaching strategy and new conceptual tools were designed to promote an enhanced understanding of the central importance of occupation to occupational therapy and, in particular, the role of participation in occupations in forming and reforming an individual within unique contextual situations. The inclusion of theory from disability studies and the use of a transformative approach to higher education were also investigated. Findings and discussion: The study spans 16 cohorts of students and reflects on the findings, which include increased client-centredness and greater appreciation of the complex nature of participation and its role in health and wellbeing.